Presentation-based Macromedia Flash Design on Static Electricity Material for Junior High School Students - Fitri April Yanti; M Anas Thohir; Moh Irma Sukarelawan; Hendri Noperi (Universitas Lambung Mangkurat, 2023)
The study aimed to design a presentation-based macromedia flash on static electricity for junior high school students. This study uses the type of research and development. The ADDIE model was chosen in this study, which includes: analysis, design, development, implementation, and evaluation. However, the design stage is carried out in 3 stages: analysis, design, and development. The research data were obtained by reviewing the curriculum, interviews, and validation questionnaires. There were 9 students in class IX who were subject to a limited trial in this study. Data was analysed by reviewing the curriculum contents, descriptive interview results, and quantitative analysis for validation results. The results showed that the presentation-based macromedia flash design results on static electricity material for junior high school students were declared valid and could be used by junior high school students. It was concluded that the results of the presentation-based macromedia flash design as a learning medium for static electricity material were accurate and could be utilized by junior high school students.